Analyzing the impact of public transit usage on obesity - SHE, Zhaowei (Institutional Knowledge at Singapore Management University, 2017)
The objective of this paper is to estimate the impact of county-level public transit usage on obesity prevalence in the United States and assess the potential for public transit usage as an intervention for obesity. This study adopts an instrumental regression approach to implicitly control for potential selection bias due to possible differences in commuting preferences among obese and non-obese populations. United States health data from the 2009 Behavioral Risk Factor Surveillance System and transportation data from the 2009 National Household Travel Survey are aggregated and matched at the county level. County-level public transit accessibility and vehicle ownership rates are chosen as instrumental variables to implicitly control for unobservable commuting preferences. The results of this instrumental regression analysis suggest that a one percent increase in county population usage of public transit is associated with a 0.221 percent decrease in county population obesity prevalence at the α = 0.01 statistical significance level, when commuting preferences, amount of non-travel physical activity, education level, health resource, and distribution of income are fixed. Hence, this study provides empirical support for the effectiveness of encouraging public transit usage as an intervention strategy for obesity.